Improving Lecturer Performance: The Role Of Locus Of Control, Motivation And Competence - Mochammad Munir Rachman; Sugijanto; Ch. Menuk Handayani (Jurnal Manajemen, 2022)
This study aims to discuss the performance of lecturers, because the locus of control plays a role in improving their performance, and is supported by motivation and competence. With the explanatory method, 200 samples were obtained from distributing questionnaires and using SEM analysis. As a result, locus of control has an effect on motivation and competence and has a negative effect on lecturer performance. It is characterized by the absence of changes in behaviour and attitudes, they still expect fate, luck, and other support for closeness to the ruler, external support is stronger than internal locus of control. They prefer to wait for the actions of others, as long as they can meet their performance needs. Motivation and competence have a fairly good influence in supporting their performance improvement. This situation occurs because their belief, effort, ability, and independence in producing a successful performance are still weak compared to fate.